Step
*
1
of Lemma
int-to-ring-mul
1. r : Rng
2. a1 : ℤ
3. a2 : ℤ
⊢ int-to-ring(r;a1 * a2) = (int-to-ring(r;a1) * int-to-ring(r;a2)) ∈ |r|
BY
{ ((Assert ⌜∀n:ℕ. ∀x:ℤ.  (|x| < n 
⇒ (∀y:ℤ. (int-to-ring(r;x * y) = (int-to-ring(r;x) * int-to-ring(r;y)) ∈ |r|)))⌝⋅
   THENM (InstHyp [⌜|a1| + 1⌝;⌜a1⌝;⌜a2⌝] (-1)⋅ THEN Auto)
   )
   THEN InductionOnNat
   THEN Auto') }
1
1. r : Rng
2. a1 : ℤ
3. a2 : ℤ
4. n : ℤ
5. 0 < n
6. ∀x:ℤ. (|x| < n - 1 
⇒ (∀y:ℤ. (int-to-ring(r;x * y) = (int-to-ring(r;x) * int-to-ring(r;y)) ∈ |r|)))
7. x : ℤ
8. |x| < n
9. y : ℤ
⊢ int-to-ring(r;x * y) = (int-to-ring(r;x) * int-to-ring(r;y)) ∈ |r|
Latex:
Latex:
1.  r  :  Rng
2.  a1  :  \mBbbZ{}
3.  a2  :  \mBbbZ{}
\mvdash{}  int-to-ring(r;a1  *  a2)  =  (int-to-ring(r;a1)  *  int-to-ring(r;a2))
By
Latex:
((Assert  \mkleeneopen{}\mforall{}n:\mBbbN{}.  \mforall{}x:\mBbbZ{}.
                        (|x|  <  n  {}\mRightarrow{}  (\mforall{}y:\mBbbZ{}.  (int-to-ring(r;x  *  y)  =  (int-to-ring(r;x)  *  int-to-ring(r;y)))))\mkleeneclose{}\mcdot{}
  THENM  (InstHyp  [\mkleeneopen{}|a1|  +  1\mkleeneclose{};\mkleeneopen{}a1\mkleeneclose{};\mkleeneopen{}a2\mkleeneclose{}]  (-1)\mcdot{}  THEN  Auto)
  )
  THEN  InductionOnNat
  THEN  Auto')
Home
Index